Young political consumers between the individual and the collective: evidence from the UK and Greece. (3rd July 2022) - Kyroglou, Georgios; Henn, Matt
ABSTRACT: The perceived surge of young people's interest and engagement in politics as a result of their pro-environmental attitudes and cosmopolitan orientation has been recently well-documented. However, one form of youth political participation which remains particularly understudied is political consumerism. Consequently, we still know relatively little about what motivates young people to engage in it, or the extent to which these motivations vary across countries. Although previous literature perceives political consumerism as a primarily individualistic form of political participation, we argue that such conceptualisations underestimate the growth of political communities of citizens-consumers. Using a unique survey of 634 young people aged 18–29, we examine the diversity of personal motivations and the personality outreach of young political consumers in a country of the European north (the United Kingdom), and one of the European south (Greece). The data reveal that young political consumers are operating less from an exclusively individualist position and more from a 'connected' one. Indeed, their personality orientation outlook reaches beyond their immediate local communities, to an ever-expanding global imagined community. In turn, their motivations seem to expand even further, involving also the animal kingdom and the wider environment.